Social Class and State Power Exploring an Alternative Radical Tradition (Springer International Publishing, 2018)
This book explores the idea of social class in the liberal tradition. It collects classical and contemporary texts illustrating and examining the liberal origins of class analysis-often associated with Marxism but actually rooted in the work of liberal theorists. Liberal class analysis emphasizes the constitutive connection between state power and class position. Social Class and State Power documents the rich tradition of liberal class theory, its rediscovery in the twentieth century, and the possibilities it opens up for research in the new millenium.